A SURVEY OF UNEMPLOYMENT RELIEF IN CANADA - Smith, Elizabeth H. (My University, 1935)
The problem of unemployment relief has recently become of national importance to Canada. The rapid industrialization of Canada in the past few decades and the attendant increase in population have brought Canada face to face with the periodic mass unemployment characteristic of the modern industrial system. It has been attempted here to trace the development of the relief program in Canada and while the study docs not by any means exhaust the subject it has been undertaken with a view towards the emphasis of certain salient features and points have grown directly out of the Canadian situation. The Canadian policy towards unemployment relief has always been, and to a large extent still is, characterized by its experimental and emergency nature. This is quite evident when the programs of the years 1930-1934· are considered and the Vacillation and revisal of policy is observed, We have gone from Public Works to Direct Relief and in the year 1934, not covered in this report, there was experienced another policy. At this time the sum of $40,000,000 was voted by the Dominion Government for the construction of federal public works throughout the country.(l) The government has continued to add new elements and a now emphasis from time to time changes the direction of relief policy. Unemployment insurance has teen introduced, inflation has been bandied with and suggestions and changes continue to follow upon one another. The final word cannot by any means be said (regarding unemployment relief) and it is with the intention primarily to clarify certain aspects of the Canadian problem and to thereby develop a constructive approach that this study is undertaken.
Keywords: Political